Toy story a critical reading - Kemper, Tom (BFI film classics, 2015)
"The first computer-generated animated feature film, Toy Story (1995) sustains a dynamic vitality that proved instantly appealing to audiences of all ages. Like the great Pop Artists, Pixar Studios affirmed the energy of modern commercial popular culture and, in doing so, created a distinctive alternative to the usual Disney formula. Tom Kemper traces the film's genesis, production history and reception to demonstrate how its postmodern mishmash of pop culture icons and references represented a fascinating departure from Disney's fine arts style and fairytale naturalism. By foregrounding the way in which Toy Story flipped the conventional relationship between films and their ancillary merchandising by taking consumer products as its very subject, Kemper provides an illuminating, revisionist exploration of this groundbreaking classic."--Page [4] of cover